2020
DOI: 10.1093/mnras/staa3750
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stars as standard candles – II. The median J magnitude as a distance indicator

Abstract: We introduce a new distance determination method using carbon-rich asymptotic giant branch stars (CS) as standard candles and the Large and Small Magellanic Clouds (LMC and SMC) as the fundamental calibrators. We select the samples of CS from the ((J − Ks)0, J0) colour–magnitude diagrams, as, in this combination of filters, CS are bright and easy to identify. We fit the CS J-band luminosity functions using a Lorentzian distribution modified to allow the distribution to be asymmetric. We use the parameters of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 95 publications
4
26
0
Order By: Relevance
“…We then went on to apply the JAGB method to a significantly more distant galaxy, NGC 253, obtaining a JAGB distance of 3.40 Mpc, which is close to its TRGB distance of 3.46 Mpc (Dalcanton et al 2009). We note also that a growing number of authors (Ripoche et al 2020;Parada et al 2021;Zgirski et al 2021) have also advocated for the use of this class of carbon stars as extragalactic distance indicators with the latter paper generally confirming the earlier conclusions and calibrations.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…We then went on to apply the JAGB method to a significantly more distant galaxy, NGC 253, obtaining a JAGB distance of 3.40 Mpc, which is close to its TRGB distance of 3.46 Mpc (Dalcanton et al 2009). We note also that a growing number of authors (Ripoche et al 2020;Parada et al 2021;Zgirski et al 2021) have also advocated for the use of this class of carbon stars as extragalactic distance indicators with the latter paper generally confirming the earlier conclusions and calibrations.…”
supporting
confidence: 78%
“…Attempting to go further in adjusting the parameters, we believe, would be pushing these datasets too hard. For the findings made by others grappling with these same problems, we refer the reader to the papers by Parada et al (2021) and Zgirski et al (2021).…”
Section: Methodsmentioning
confidence: 96%
“…We note that other groups have used a slightly different procedure for measuring the apparent JAGB magnitude than that described above. Ripoche et al (2020) and Parada et al (2021) fit a modified Lorentzian distribution to the observed JAGB LF using a maximum likelihood estimator to measure the median magnitude. Zgirski et al ( 2021) also fit a model to the observed JAGB LF, although using instead a Gaussian quadratic function.…”
Section: Groundmentioning
confidence: 99%
“…We generated the theoretical stellar isochrones using the PARSEC-COLIBRI software 8 (CMD Version 3.6; Bressan et al 2012;Marigo et al 2017) to study the JAGB's expected theoretical behavior, similar to the analysis performed by Parada et al (2021). We generated isochrones of stars in the TP-AGB phase with a range of metallicities spanning −1 < [M/H] < 0 dex and ages spanning 1.5 − 2.5 × 10 9 years, where carbon star formation is strongly favored (Marigo 2015;Marigo et al 2017), shown in Figure 6.…”
Section: Hstmentioning
confidence: 99%
“…They found measurements consistent with those of nearby dwarf galaxies and also the first evidence of the knee in the [α/Fe] versus [Fe/H] relation. d) NGC 6822 thanks to its modest distance has been the cross road of multi-band investigations ranging from the optical to the near-infrared (NIR) and to the mid-infrared (MIR) of Young Stellar Objects (YSO) and Asymptotic Giant Branch (AGB) stars (Letarte et al 2002, hereinafter L02;Kinson, Oliveira & van Loon 2021;Parada et al 2021). These investigation have been soundly complemented by low- (Kacharov, Rejkuba & Cioni 2012, hereinafter K12) and mediumresolution spectroscopy (Sibbons et al 2012(Sibbons et al , 2015S15).…”
Section: Introductionmentioning
confidence: 99%